Karakteristik Kimia dan Sensori Stik Bawang dengan Penambahan Tepung Ikan Lele Dumbo (Clarias gariepinus) - Vika Ramadani; Titi Rohmayanti; Siti aminah (Universitas Djuanda, 2024)
Churros is a food from Spain which is currently popular in Indonesia. Taro flour is a substitute for wheat flour because wheat flour has more calories than taro flour and the addition of Bogor bean flour to making churros can increase the protein in churros. This research aims to innovate churros products based on local food ingredients. This research used a completely randomized design (CRD) consisting of four treatment levels and two replications. The treatment consisted of a comparison of taro flour and Bogor bean flour (100% : 0%), (70% : 30%), (50% : 50%), (30% : 70%). Chemical analysis includes moisture content, ash content, fat content, protein and carbohydrate content as well as sensory and hedonic quality tests to determine the selected product. The research data analysis used was (ANOVA) with Duncan's Advanced Test with a 95% confidence interval. The results showed that the churros selected in the ratio of taro flour and Bogor bean flour (70% : 30%) had a moisture content of 17.70%, ash content of 1.95%, fat content of 12.79%, protein content of 8.98%, carbohydrate content 58.58%. Churros from taro flour with substitution of Bogor bean flour have a texture that tends to be crunchy, the color tends to be brownish yellow, the aroma is not bad, the taste tends to be sweet, the aftertaste is not bitter.